Produtividade de milho sob plantio direto em dois espaçamentos no semiárido Potiguar - Leitão, Erllan Tavares Costa (2020)
Due to the scarcity of rain and high temperatures, the semi-arid region of the Northeast may present itself as a limitation for plant production. It is therefore important to study the best methodologies for using this technique for the conditions of the semiarid region. In view of the above, this study aimed to evaluate the productive performance of irrigated corn under no-tillage in an argisolic red dystrophic oxisol, from the semi-arid region located in the municipality of Mossoró / RN. The experimental design used was 2 x 2; being a BRS Gorutuba cultivar and a BRS 2022 hybrid.The other source of variation was the line spacing being used 0.45 and 0.90 m, totaling four treatments in random blocks with seven repetitions, composing 28 experimental units. The dimensions are 30 meters long and 6 meters wide, totaling 180 m². The soil layers analyzed were: 0.00-0.15 and 0.15-0.30m.The productivity data obtained were submitted to analysis of variance, F test and for the spacing factor and test of comparison of means; from the data of productivity the data of the chemical analyzes of the soil was analyzed using the program Sisvar 4.0.According to the results of the analysis of variance, there was a significant effect at the 1% probability level when the cultivars were analyzed separately, for the variables number of plants per hectare, number of ears per hectare and productivity. Regarding the spacing factor, there was a significant effect at the level of 5% probability for the variables plants per hectare and ears per hectare.Yield did not differ statistically in the comparison between the two spacing or the cultivar X hybrid relationship, both produced on average one ear per plant regardless of the treatment. Regarding the productive performance, it is concluded that the hybrid BRS2022 presented a higher number of plants and ears than the BRS Gorutuba, it was found that this performance is directly related to the greater number of plants in the final stand of the first cultivar than the second